1986
DOI: 10.1055/s-2007-1020390
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow during Early Cardiopulmonary Bypass in Man. Effect of Procaine in Cardioplegic Solutions

Abstract: Cerebral blood flow (CBF), plasma procaine concentrations, and somatosensory evoked potentials (SSEP) were recorded in 2 groups of patients in whom either a high-procaine cardioplegic solution (Bretschneider's n = 29), or a low-procaine cardioplegic solution (St. Thomas', n = 13) was used. In the Bretschneider's group, marked changes in CBF occurred (p less than 0.001). Mean CBF was 27 (range 18 to 51) ml/(100 g X min) between sternotomy and the onset of extracorporeal circulation (ECC). A mean of 6 minutes af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The effect is transient, however, and is noticed only during hypothermic bypass, just after the infusion of the cardioplegic solution. 8 Given that arterial filters of 20 or 40 microns slightly reduced cerebral blood flow but did not prevent brain hyperaemia and filters of even smaller pore size would probably result in too much blood trauma, some other measure is needed to reduce cerebral blood flow. Management of PCo2 could be a simpk way of doing this, and hence appreciably reduce the amount of emboli which could be trapped in the brain capillaries.…”
Section: Effect Of Arterial Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect is transient, however, and is noticed only during hypothermic bypass, just after the infusion of the cardioplegic solution. 8 Given that arterial filters of 20 or 40 microns slightly reduced cerebral blood flow but did not prevent brain hyperaemia and filters of even smaller pore size would probably result in too much blood trauma, some other measure is needed to reduce cerebral blood flow. Management of PCo2 could be a simpk way of doing this, and hence appreciably reduce the amount of emboli which could be trapped in the brain capillaries.…”
Section: Effect Of Arterial Filtrationmentioning
confidence: 99%
“…A new index of the quality of surgery is emerging, based on psychometric analysis of the extent to which complex mental functioning is preserved in the early postoperative period, combined with more quantitative methods, such as analysis of spinal fluid intracellular markers1 -3 and measurements of cerebral blood flow during and after cardiac surgery. [4][5][6][7][8] In our earlier studies of cerebral blood flow during cardiac surgery we found a consistent hyperperfusion of the brain during cardiopulmonary bypass6 -8 and a diffusely reduced regional cerebral blood flow after surgery,5 the most reasonable explanation being a diffuse microvascular blockage of microembolic origin.…”
mentioning
confidence: 99%
“…patient on Jan 15. th 2005 in his hospital bedOn day 17 cervical fixation and stabilization (at spinal vertebrae C2-C3 the site of dislocationFig 2)was done by the neurosurgeon.…”
mentioning
confidence: 99%